Sorting Nexin 1 Loss Results in D(5) Dopamine Receptor Dysfunction in Human Renal Proximal Tubule Cells and Hypertension in Mice - Villar, Van Anthony M. (American Society for Biochemistry and Molecular Biology, 2013)
The peripheral dopaminergic system plays a crucial role in blood pressure regulation through its actions on renal hemodynamics and epithelial ion transport. The dopamine D5 receptor (D(5)R) interacts with sorting nexin 1 (SNX1), a protein involved in receptor retrieval from the trans-Golgi network. In this report, we elucidated the spatial, temporal, and functional significance of this interaction in human renal proximal tubule cells and HEK293 cells stably expressing human D(5)R and in mice. Silencing of SNX1 expression via RNAi resulted in the failure of D(5)R to internalize and bind GTP, blunting of the agonist-induced increase in cAMP production and decrease in sodium transport, and up-regulation of angiotensin II receptor expression, of which expression was previously shown to be negatively regulated by D(5)R. Moreover, siRNA-mediated depletion of renal SNX1 in C57BL/6J and BALB/cJ mice resulted in increased blood pressure and blunted natriuretic response to agonist in salt-loaded BALB/cJ mice. These data demonstrate a crucial role for SNX1 in D(5)R trafficking and that SNX1 depletion results in D(5)R dysfunction and thus may represent a novel mechanism for the pathogenesis of essential hypertension.